2018
DOI: 10.1210/en.2018-00338
|View full text |Cite
|
Sign up to set email alerts
|

ACC2 Deletion Enhances IMCL Reduction Along With Acetyl-CoA Metabolism and Improves Insulin Sensitivity in Male Mice

Abstract: Intramyocellular lipid (IMCL) accumulation in skeletal muscle greatly contributes to lipid-induced insulin resistance. Because acetyl-coenzyme A (CoA) carboxylase (ACC) 2 negatively modulates mitochondrial fatty acid oxidation (FAO) in skeletal muscle, ACC2 inhibition is expected to reduce IMCL via elevation of FAO and to attenuate insulin resistance. However, the concept of substrate competition suggests that enhanced FAO results in reduced glucose use because of an excessive acetyl-CoA pool in mitochondria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
2
10
1
1
Order By: Relevance
“…There is also a decrease in Acacb, which encodes the protein ACC2, a rate limiting step in fatty acid uptake and oxidation in the mitochondria, in female IL1R1 −/− groups irrespective of maternal diet. Depletion of this protein improves overall metabolic health in mice fed a HFD (Takagi et al, 2018). Furthermore, there was a decrease in expression of Acsl1, which encodes a protein which mediates the conversion of long-chain fatty acids to fatty acyl-CoA esters producing important substrates for mitochondrial fatty acid biosynthesis, in IL1R1 −/− groups irrespective of genotype.…”
Section: Discussionmentioning
confidence: 96%
“…There is also a decrease in Acacb, which encodes the protein ACC2, a rate limiting step in fatty acid uptake and oxidation in the mitochondria, in female IL1R1 −/− groups irrespective of maternal diet. Depletion of this protein improves overall metabolic health in mice fed a HFD (Takagi et al, 2018). Furthermore, there was a decrease in expression of Acsl1, which encodes a protein which mediates the conversion of long-chain fatty acids to fatty acyl-CoA esters producing important substrates for mitochondrial fatty acid biosynthesis, in IL1R1 −/− groups irrespective of genotype.…”
Section: Discussionmentioning
confidence: 96%
“…Повышенная экспрессия гена Acacb (ацетил-коэнзим А карбоксилаза бета), рассматриваемого в качестве регулируемого AMPK (cAMP-activated protein kinase) промотера липогенеза и фактора, препятствующего митохондриальному β-окислению жирных кислот [25,26], отмечалась у db/db-мышей, получавших Q, в то время как ответ этого гена у мышей C57Bl/6J был противоположным. Малонил-КоА, генерируемый ацетил-КоА-карбоксилазами, является ключевым метаболитом в синтезе жирных кислот.…”
Section: Discussionunclassified
“…BKS.Cg-1Lepr db /1Lepr db /Jcl (db/db) mice and their nondiabetic controls (db/m) were obtained from CLEA Japan (Tokyo, Japan). ACC2 knockout mice and wild-type mice were generated as previously described (Takagi et al, 2018). All studies were performed using male animals.…”
Section: Animal Studiesmentioning
confidence: 99%
“…2000; Brownsey et al, 2006;Wakil and Abu-Elheiga, 2009). Though whole-body deletion of ACC1 in mice is embryonic lethal (Abu-Elheiga et al, 2005), deletion of ACC2 in mice has been reported to decrease lipid accumulation by enhancing FAO in skeletal muscle and improve whole-body insulin resistance (Choi et al, 2007;Takagi et al, 2018). Pharmacological selective inhibition of ACC2 is thus currently regarded as a hopeful avenue for the therapy of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation